The new fiscal rules: Another round of austerity for Europe? - Christoph Paetz; Sebastian Watzka (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2024)
This policy brief presents the new EU fiscal rules with a focus on its core element, the so-called debt-sustainability-analysis (DSA). Our results suggest first that the new rules will lead to substantial fiscal consolidation in the next years albeit less severe than the austerity measures during the euro crisis, second that the new rules are far less beneficial for public investment than previously thought, and third that relatively minor changes to the DSA assumptions on ageing costs and interest rates can have important consequences for fiscal adjustment needs. However, even if some of the assumptions underlying the DSA methodology were to be changed, the additional fiscal space would still fall drastically short of the massive public investment needs of the EU's green transition. We conclude by making the case for an EU-wide debt-financed investment fund.
Keywords: 330; EU Fiscal rules; fiscal rules; debt-sustainability analysis; DSA; ageing costs; green transition